Grit and Its Related Factors in Undergraduate Students - Hira Arif, Muhammad Umar Khan; Qasir Abbas (Pakistan Journal of Clinical Psychology, 2021)
Objectives: Grit is the ability to stay consistent and determined toward long term goals, even after facing many obstacles and failures while also maintaining the ability to resist defeat. The current study explored grit, as it manifests itself in Pakistani milieu among undergraduate students. Design of the study: There was no qualitative study was found on google scholar on grit in Pakistani context. The purpose of this study was to capture the conceptualization of grit in Pakistan. Method: The current study was exploratory qualitative study utilizing thematic analysis. The sample of the study was 18 undergraduate students with the age range of 17 to 25 years; they were approached from different universities, colleges. Universities and college students were contacted through email asking them to take part in a study. Purposive sampling was used for the selection of participants. Participants filled the grit questionnaire designed by Angela Duckworth (2016). After finding out the level of grit, participants with higher levels of grit were requested for an in-depth interview. Findings: Thematic analysis method was used to analyze the interviews. Six super themes named ‘passion and perseverance, social support, growth mindset, self-control, role of environment and religiosity’ emerged as the factors affecting grit of Pakistani undergraduate students. Conclusion: This study showed the characteristics of grit as manifested by Pakistani undergraduate students which includes some already known aspects like passion, perseverence, social support, self control and some novel aspects like role of environment, growth mindset and religiosity.